The Influence Of Marketing Mix On Student Trust and Its Impact on Competitive Advantage Of Private Higher Education Institution - Sama, Hendi; Brahmasari, Ida Aju; Ratih, Ida Aju Brahma (Archives of Business Research, 2017)
The purpose of this research is to construct a new concept about the influence of marketing mix to trust and trust towards the competitive advantage of private higher education. The research method of gathering data in this research is by conducting quantitative research. The dissemination of the survey is using simple random sampling at private higher education in Kepri province of Indonesia. Respondents from this research are 425 students representing all students of private higher education located in Kepri. The results are Marketing Mix has significant influence to the trust toward private higher education in Kepri province and Trust has a significant effect on the Competitive Advantage of private higher education in Kepri Province. The research concludes that private higher education in Kepri provinces should pay attention to the effect of marketing mix and trust in order to have a suitable competitive advantage.